The results of experimental testing conceptual model of the development of information and communication competence of philological disciplines teachers’ in the system of postgraduate education - Degtyaryova, G. (Problems of Engineer-Pedagogical Education, 2018)
The modern information society requires from competent ICT teachers. This prompted the study of the theoretical and methodological foundations for the development of the IС competence of teachers and development of a conceptual model of the development of this competence of teachers of philological disciplines in the system of postgraduate education. During 2012-2016, this model was tested in the Kharkov Academy of continuous education and seven institutions of postgraduate pedagogical education. The activity of subjects (364 of the teacher-philologists in the experimental and control groups) for the development of IC skills was studied in an environment close to everyday life, in familiar types and forms of activities in course and intercourse periods. The study was based on a set of methods (theoretical, empirical and mathematical statistics methods), the use of which allowed to determine the effectiveness of the implementation of the system of postgraduate education the conceptual model of the development of the IC competence of teachers of linguistic disciplines. The article considers the results of monitoring the impact of the participation of teachers-philologists in different forms and types of activities on the development and degree of manifestation of IC competence. We came to the conclusion that the level of IC competence will grow if in the system of postgraduate education training teachers-philologists in the field of ICT to build on our developed model.